Chemical scarification using kno3 to increase seed germination and early growth of Indigofera zollingeriana - E Simbolon; T H Wahyuni; N D Hanafi; Hamdan; Y L Henuk; N Ginting (Talenta Publisher, 2019)
Indigofera zollingeriana as animal feed contain high protein and a goodalternative source of feed for livestok. In North Sumatera Province, now adaysIndigofera has been introduced to livestockers. This study aims to determine theeffect of scarification by soaking KNO3 (potassium nitrate) on seed germination andearly growth of Indigofera zollingeriana. This research was carried out at AnimalProduction Laboratory; Animal Husbandry Study Program, Faculty of Agriculture,University of North Sumatra Jl. A. Sofyan No. 3 Medan, which began from November2018 to January 2019. The design used was a factorial completely randomized design(RAL) with 12 combination factors, each of which contained 3 replications where eachreplication contained 15 seeds of Indigofera zollingeriana. The treatment consisted of2 factors, namely the K factor = KNO3 concentration, K0 = control, K1 = 4 g / l, K2 =8 g / l, K3 = 12 g / l repeatedly, and L factor = soaking time, L1 = 4 hours, L2 = 8hours, L3 = 12 hours .The results showed that the administration of KNO3 and soaking time on Indigoferazollingeriana seeds had a significant effect on the percentage of sprouts, sprout height,and growing power. The conclusion of the use of KNO3 with levels of 4 grams and 8grams has a positive impact on the percentage of germination and height of indigoferazollingeriana and the duration of 12 hours immersion in the seeds of indigoferazollingeriana also gives a positive effect on the percentage of sprouts and sproutheight, and the best percentage of growth is on the use of 8 grams of KNO3 with 8hours of soaking time.